2020
DOI: 10.1080/13696998.2020.1737535
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing individuals’ take-up of tax-subsidized private health insurance: a cross-sectional study in China

Abstract: Aims: To identify factors influencing individuals' take-up of tax-subsidized private health insurance. Methods: A self-administered questionnaire survey was conducted to collect data in Hangzhou, China. A logistic regression analysis was applied to find factors influencing individuals' take-up of tax-subsidized private health insurance. Results: A total of 1,610 participants joined the survey, and 1,543 valid cases were obtained. The logistic regression results showed that educational level, marital status, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, SBMI is limited in service coverage and reimbursement. It is difficult for SBMI to meet enrollees' growing needs for higher quality medical services [10]. While PHI can provide a broader range of coverage options [5], the central government has begun to attach importance to developing PHI since 2014.…”
Section: Introductionmentioning
confidence: 99%
“…However, SBMI is limited in service coverage and reimbursement. It is difficult for SBMI to meet enrollees' growing needs for higher quality medical services [10]. While PHI can provide a broader range of coverage options [5], the central government has begun to attach importance to developing PHI since 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Educational levels also had no association with PHI uptake among the east coast populations in Malaysia despite many studies showing contradicting findings [ 13 , 16 , 17 ]. However, participants who attained tertiary education had a higher percentage of PHI uptake compared to those with secondary education or below.…”
Section: Discussionmentioning
confidence: 92%
“…Women in Brazil had higher insurance health coverage [ 12 ], while in Namibia, the proportion of PHI ownership was higher among men [ 14 ]. However, studies in China and India showed that the proportions of PHI ownership among males and females were equivalent [ 13 , 15 , 16 ]. A higher educational level is usually associated with better employment with promising salary prospects and better health literacy that increases the likelihood of obtaining accurate information on health status and services.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations